Sublingual apomorphine (APL‐130277) for the acute conversion of OFF to ON in Parkinson's disease. Issue 9 (19th July 2016) - Hauser, Robert A.; Olanow, C. Warren; Dzyngel, Bruce; Bilbault, Thierry; Shill, Holly; Isaacson, Stuart; Dubow, Jordan; Agro, Albert
ABSTRACT: Introduction: OFF episodes negatively impact quality of life in patients with Parkinson's disease (PD). There remains a need for an acute, effective, noninvasive treatment. Background: APL‐130277 is a sublingually administered apomorphine oral strip. Methods: The authors conducted a phase 2, open‐label, proof‐of‐concept study. Patients presented to clinic in the morning in the practically defined OFF state and were dosed with APL‐130277 10 mg. Assessments of OFF or ON state and MDS‐UPDRS part III were conducted predose and at 15, 30, 45, 60, and 90 minutes. If a full ON was not achieved within 3 hours, the dose was increased in 5 mg increments until a full ON was achieved or to a maximum dose of 30 mg. Patients could be dosed up to two times a day over 3 days. Patients were pretreated with trimethobenzamide for 3 days, which was continued during the study. Results: Of 19 patients, 15 (78.9%) achieved a full ON response. All 15 achieved a full ON response within 30 minutes and 6 of the 15 patients (40.0%) achieved a full ON response within 15 minutes. The mean (SD) duration of ON was 50 (19.4) minutes. Of the 15 patients, 9 (60.0%) remained fully ON for ≥90 minutes. There were no discontinuations as a result of an adverse event. The most common adverse events were dizziness (36.8%), somnolence (31.6%), and nausea (21.1%). Conclusion: This was the first study of a new sublingual apomorphine formulation in PD patients. In this open‐label study, APL‐130277 appeared to provide a convenient, rapid, and reliable method for treating OFF episodes. © 2016 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society